QED vacuum fluctuations and induced electric dipole moment of the neutron - Dominguez, C. A. (2009)
Quantum fluctuations in the QED vacuum generate nonlinear effects, such as peculiar induced electromagnetic fields. In particular, we show here that an electrically neutral particle, possessing a magnetic dipole moment, develops an induced electric dipole-type moment with unusual angular dependence, when immersed in a quasistatic, constant external electric field. The calculation of this effect is done in the framework of the Euler-Heisenberg effective QED Lagrangian, corresponding to the weak field asymptotic expansion of the effective action to one-loop order. It is argued that the neutron might be a good candidate to probe this signal of nonlinearity in QED.